Developing a service for the personalisation of running shoes - Matthew J. Head (2012)
The aim of this research was to specify and develop a service that is capable of delivering personalisable running shoes with mass appeal. Current sports footwear personalisation services focus primarily on aesthetic design via the internet. Aesthetics do not appear to be the consumers primary interest when purchasing running shoes and a large number are also reluctant to purchase online; preferring to purchase from specialist running stores where they receive the advice needed and can directly interact with the product. After reviewing the literature, it was hypothesised that the implementation of a primarily comfort and performance running shoe personalisation service with an in store fitting element, utilising additive manufacturing as an enabling technology, would give the greatest opportunity for success. Survey methods and store visits were employed that targeted both qualitative and quantitative data, exploring consumer running shoe purchase preferences, running shoe use and opinions of current personalisation services. The findings from these studies supported the previously stated hypothesis and enabled the specification of a suitable service. Subsequently, the focus of this research was the development of a toolkit, a computer-based system that enables the consumer to make their selections, the core of most of the current services. Experts in biomechanics and additive manufacturing were consulted to ensure that a feasible yet innovative solution was delivered. The resultant toolkit prototype (www.yourstep.co.uk) was tested formatively, using multiple methods and summatively with a large sample. Using the toolkit was considered an enjoyable, intuitive experience; a large percentage (69%) of summative testing participants would consider purchasing personalised running shoes using this method. The approach adopted to specify and develop this service provides a framework, based upon empirical research, for those looking to implement a practical running shoe personalisation service that meets their consumers requirements.